Comparison of two tests Latex and ELISA efficiency in Diagnosis of Toxoplasmosis in Lattakia Governorate. - سفر غيث; حسن سلمان; فيصل رضوان (Latakia University Journal -Biological Sciences Series, 2025)
The research dealt with compared and evaluated between two common tests used to detect of Toxoplasmosis, Latex agglutination test and Enzyme Linked Immunosorbant Assay test or ELISA test, in random sample of males and females attending Tishreen University Hospital in Lattakia during 2022 and 2023. The number of blood samples collected was 240 (161 females, 79 males). The results of LAT test showed that the infection rate in females during combined two years was 42.23% (68 infections), while a very small number of infections were recorded in males, amounting to only 5 infections, with a percentage of 6.32%. As for the infection rates for females during 2022 and 2023 with IgM, IgG and the two antibodies together, measured using ELISA test was 24.84%, 1.24% and 4.34% respectively, with 49 infections and a total percentage 30.43%, while for males it was 3.79%, 3.79% and 0%, with only six infections and a total percentage 7.59%. The sensitivity of ELISA test was 91.66%, while its specificity was 98.40%. Compared to the LAT test, whose sensitivity was 100% and its specificity was 90.27%. The ELISA test can be considered the most efficient and accurate in detecting Toxoplasma gondii infection, while the LAT test is only important for early detection of the disease.